Pengaruh Pelaksanaan Konseling Pemberian Makan Bayi dan Anak (PMBA) Terhadap Pengetahuan dan Sikap Ibu yang Memiliki Anak Usia 6-23 Bulan di Wilayah Kerja Puskesmas Merapi I Kabupaten Lahat Tahun 2021 - Desima Rony Asi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Improper infant feeding practices are the main direct cause of malnutrition during the first two years of life. Therefore, it is important to ensure that mothers of infants up to 2 years of age are given proper guidance on optimal feeding for infants and young children. This study aims to analyze the effect of the implementation of Infant and Young Children Feeding (IYCF) counseling on the knowledge and attitudes of mothers who have children aged 6-23 months at Merapi I Public Health Centre, Lahat Regency in 2021 and analyze the implementation of the IYCF counseling program in terms of a systems approach. This study uses a Mix Method Study Approach. The quantitative approach in this study uses a quasi-experimental approach with pre and post designs. The statistical test used in quantitative research is the Wilcoxon signed rank test and the Mann Whitney test. The results of this study state that there is a relationship between knowledge and attitudes with the implementation of the IYCF counseling program, this is based on statistical tests using the Wilcoxon signed rank test in the treatment group and the control group where the p value is less than 0.05, which is 0.000 and for the statistical test results, Mann Whitney U the test after the intervention obtained a significance value of less than 0.05, which is 0.000. For the implementation of IYCF counseling at Merapi I Public Health Centre, Lahat Regency, in terms of a systems approach, there are no policies that regulate the implementation of the program, inadequate human resources, methods that are not optimal, limited budget, and inadequate infrastructure. For the process of implementing this IYCF counseling there is no planning, there is organization, implementation that is not optimal and supervision is not carried out, so that the output from the implementation of this IYCF counseling is not optimally felt by mothers who have children aged 6-23 months at Merapi I Public Health Centre, Lahat Regency.